Collaboration the Role of Doctors and Pharmacers in Rational Preparation in Rantauprapat Hospital, Constraints and Its Efforts - Fifin Indira Lubis; Zulfendri; Jumirah (Britain International for Academic Research (BIAR) Publisher, 2020)
Rational prescribing is an important element in achieving the quality of health services which is one indicator in patient safety in hospital. The purpose of this study was to find out how the collaboration of the role of doctors and pharmacists in rational prescribing at Rantauprapat District Hospital. The research methodology uses a qualitative method with a phenomenological approach. Data was collected through in-depth interviews with doctors and pharmacists on duty at Rantauprapat District Hospital. The results showed that the form of collaboration between doctors and pharmacists in rational prescribing conducted at Rantauprapat District Hospital included: reviewing prescription contents, solving problems related to drug use and providing drug information. The results also showed that the obstacles in implementing collaborative roles of doctors and pharmacists included: the problem of the quantity of pharmacists that did not meet the standards and the limited pharmacist's knowledge of clinical pharmacy and the limited communication between doctors and pharmacists. Mitigation efforts include: recruiting pharmacists with clinical pharmacy qualifications, providing continuing education and training in clinical pharmacy to pharmacists, evaluating the implementation of pharmacy service policies in hospitals especially visits with doctors and pharmacists and building communication links between doctors and pharmacists through empowering the role of the pharmaceutical and therapeutic committee.